Effect of Different Cooling Regimens (Craniocerebral and Immersion Hypothermia, Surface Rhythmic Cold Exposures and Whole Body Cryostimulation) on Leukocyte Indices of Rat Blood - Lomako, Victoria V. (Problems of Cryobiology and Cryomedicine, 2019)
A comparative analysis of leukocyte types number in rat blood smears at the craniocerebral (CCH 32°C) and immersion (IH 27°C) hypothermia, surface rhythmic cold exposures (RCEs 5°C) and whole body cryostimulation (WBC -120°C), as well as in 24 hrs revealed the leukocytosis (at IH and 24 hrs after CCH and IH), leukopenia (at CCH, RCEs and 24 hrs after WBC), lymphopenia, an increase in band and segmented cells (under all conditions except IH) and eosinophils (only at CCH and 24 hrs after WBC). Plasmatic cells (except WBC), polychromatophilic and immature cells (immediately and in 24 hrs after CCH and IH), cytoplasm plasmatization in some leukocytes (24 hrs after CCH and IH) were observed. Leukocyte indices showed the immunoreactivity disorder, decreased allergization, activation of cell immunity, nonspecific cell protection and inflammation (under all conditions, except IH), as well as microphages (at WBC and 24 hrs after CCH and IH), an effector component of immunity (at CCH, RCEs and 24 hrs after WBC), immediate type hypersensitivity responses (except at CCH and 24 hrs after WBC). The nuclear shift index was increased (except RCEs and WBC). The adaptation index was raised only at IH. Probl Cryobiol Cryomed 2018; 28(4): 293-310